Peraturan Pemerintah Nomor 64 Tahun 2016 Sebagai Instrumen Hukum Untuk Menderegulasikan Produk Hukum Daerah - Anggi P. Sayogo (Officium Notarium, 2021)
This study aims to determine whether Government Regulation Number 64 of 2016 deregulates regional legal products related to the construction of low-income communities (MBR). This study uses a normative juridical approach as well as a qualitative approach by processing and analysing legal materials. Based on the results of the research and discussion, it can be concluded that Government Regulation Number 64 of 2016 has influenced the existence of regional regulations relating to housing development permits by reducing the validity of licensing provisions for MBR housing development. In other words, the government has carried out an executive review/administrative review through repressive supervision with the presence of this government regulation which delays the validity of a number of housing development permits for certain conditions.Key Word: Government Regulation, Deregulation, Housing, Low-Income Communities AbstrakPenelitian ini bertujuan untuk mengetahui apakah Peraturan Pemerintah Nomor 64 Tahun 2016 melakukan deregulasi terhadap produk hukum daerah yang berkaitan dengan pembangunan rumah Masyarakat Berpenghasilan Rendah (MBR). Penelitian ini menggunakan metode pendekatan yuridis normatif serta pendekatan kualitatif dengan pengolahan dan analisis bahan hukum. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa Peraturan Pemerintah Nomor 64 Tahun 2016 telah mempengaruhi eksistensi peraturan daerah yang berkaitan dengan perizinan pembangunan perumahan dengan mereduksi keberlakuan ketentuan perizinan bagi pembangunan perumahan MBR. Dengan kata lain, pemerintah telah melakukan executive review/administrative review melalui pengawasan represif dengan hadirnya peraturan pemerintah ini yang menunda keberlakuan sejumlah perizinan pembangunan perumahan untuk kondisi tertentu.Kata-kata Kunci: Peraturan Pemerintah, Deregulasi, Perumahan, Masyarakat Berpenghasilan Rendah